Functional Consequences of Substitution Mutations in MepR, a Repressor of the Staphylococcus aureus mepA Multidrug Efflux Pump Gene - Schindler, Bryan D. (American Society for Microbiology, 2013)
The expression of mepA, encoding the Staphylococcus aureus MepA multidrug efflux protein, is repressed by the MarR homologue MepR. MepR dimers bind differently to operators upstream of mepR and mepA, with affinity being greatest at the mepA operator. MepR substitution mutations may result in mepA overexpression, with A103V most common in clinical strains. Evaluation of the functional consequences of this and other MepR substitutions using a lacZ reporter gene assay revealed markedly reduced repressor activity in the presence of Q18P, F27L, G97E, and A103V substitutions. Reporter data were generally supported by susceptibility and efflux assays, and electrophoretic mobility shift assays (EMSAs) confirmed compromised affinities of MepR F27L and A103V for the mepR and mepA operators. One mutant protein contained two substitutions (T94P and T132M); T132M compensated for the functional defect incurred by T94P and also rescued that of A103V but not F27L, establishing it as a limited-range suppressor. The function of another derivative with 10 substitutions was minimally affected, and this may be an extreme example of suppression involving interactions among several residues. Structural correlations for the observed functional effects were ascertained by modeling mutations onto apo-MepR. It is likely that F27L and A103V affect the protein-DNA interaction by repositioning of DNA recognition helices. Negative functional consequences of MepR substitution mutations may result from interference with structural plasticity, alteration of helical arrangements, reduced protein-cognate DNA affinity, or possibly association of MepR protomers. Structural determinations will provide further insight into the consequences of these and other mutations that affect MepR function, especially the T132M suppressor.